Oceanographic Data of the 54th Japanese Antarctic Research Expedition from December 2012 to March 2013 - SHIMOMURA, Hiroki (国立極地研究所, 2016)
Fig. 1 | http://polaris.nipr.ac.jp/~parc/pub/v027/nipr_parc_200_0007.xlsx Table 1 | http://polaris.nipr.ac.jp/~parc/pub/v027/nipr_parc_200_0008.xlsx Table 2 | http://polaris.nipr.ac.jp/~parc/pub/v027/nipr_parc_200_0009.docx Table 3 | http://polaris.nipr.ac.jp/~parc/pub/v027/nipr_parc_200_0010.xlsx Table 4 | http://polaris.nipr.ac.jp/~parc/pub/v027/nipr_parc_200_0011.docx departmental bulletin paper